Cardiovascular responses and cybersickness induced by virtual reality in undergraduate medical students. - Peñúñuri-Domínguez , José Alfredo; González-Flores, Andrea; Alvarado-Mena, Ignacio; Hernández-Albarrán, Nadia Arleth; Cerón-Apipilhuasco , Ariana; Loria-Castellanos, Jorge; Mendoza-Carrillo, Juan Rodrigo; Teodoro-Vite, Sergio; Fuertes Abascal, Begoña; Iñigo-Cabrejos, Rubén Dario (Spanish Journal of Medical Education, 2026)
Introduction: Virtual reality (VR) is an emerging technological and educational resource that is increasingly being used in medical education for the development of technical skills through an immersive environment. VR has shown clinical benefits in reducing perioperative anxiety in patients and also allowing educational experiences to pregrade students on different topics like anatomy and basic life support training. Even though VR has benefits, adverse effects such as cybersickness have been reported, with limited evidence regarding the exposure time for onset and its physiological impact. Measuring and analyzing these parameters is important to establish safe exposure times for VR simulations. Objective: Evaluate changes in heart rate, blood pressure, and cybersickness symptoms after a 15-minute exposure to a VR environment (Anatomy and Physiology Lab on META Quest 2) in pre-graduate medical students, by comparing physiological parameters and applying the Simulator Sickness Questionnaire (SSQ) before and after immersion. Methods: Observational, descriptive, cross-sectional study in which vital signs (heart rate, respiratory rate, and blood pressure) were recorded before and after exposure to a VR environment. The qualitative data were analyzed using frequencies and percentages, and the quantitative data with medians and ranges. Chi-square and Student’s t tests were applied to assess differences between time points. Results: No significant changes were found in heart rate (p = 0.1754). Respiratory rate increased after exposure (p = 0.0017), as did systolic blood pressure (p = 0.0329), while diastolic pressure remained unchanged (p = 0.7025). Regarding cybersickness, symptoms occurred in 20% of participants, with no association to VR experience (p > 0.05). Conclusions: VR exposure may increase respiratory rate and systolic blood pressure without affecting heart rate. Further research is needed to determine optimal immersion duration and predisposing factors that may contribute to adverse effects in order to ensure a safe and effective immersive experience in medical education.